NSAID use increases the risk of developing hyponatremia during an Ironman triathlon - Wharam, P. C.; Speedy, D. B.; Noakes, T. D.; Thompson, J. M. D.; Reid, S. A.; Holtzhausen, L. M. (Medicine & Science in Sports & Exercise, 2006)
Purpose: Exertional hyponatremia ((Na) < 135 mmol[middle dot]L-1) is a potentially serious condition associated with endurance sports. It has been postulated that nonsteroidal antiinflammatory drug (NSAID) use may be a risk factor. This observational cohort study aimed to determine whether NSAID use is a risk factor for exertional hyponatremia and altered renal function during endurance exercise.